Factors associated with cervical cancer screening among women of reproductive age in Moshi municipality, Kilimanjaro, Tanzania: a cross-sectional study - Sia E Msuya; Jeremiah John Hhera; Regina Dahaye; Witness Erasto Zakayo; Yohana Z Kazula; Seif Abdul; Redempta Mamseri (BMJ Open)
Objective Screening for cervical cancer has been a globally advocated preventive strategy to reduce cervical cancer morbidity and mortality. This study aimed to describe the prevalence and barriers of cervical cancer screening, and to determine factors associated with cervical cancer screening among women of reproductive age in Moshi municipality, northern Tanzania.Design We conducted a cross-sectional study between August and September 2020.Setting Moshi municipality, Kilimanjaro, Tanzania.Participants Women of ages 15–49 years who live in Moshi municipality.Results A total of 300 women participated in the study and 22.7% had ever been screened for cervical cancer. Women below the age of 30 years had 87% lower odds of screening for cervical cancer compared with those aged 30 years and above (OR 0.13; 95% CI 0.04, 0.43). Women who had never heard about cervical cancer had 94% (OR 0.06; 95% CI 0.01, 0.51) lower odds of screening compared with those who ever heard about the disease. In comparison to married women, those who identified as single had 71% lower odds of screening for cervical cancer (OR 0.29; 95% CI 0.10, 0.73). Women without formal education or with only primary-level education had 72% lower odds of screening for cervical cancer compared with those with college or university education (OR 0.28; 95% CI 0.08, 0.98). A lack of awareness on where to screen and a lack of comprehensive knowledge about cervical cancer were reported as screening barriers among those who had never been tested.Conclusion Only one in five women have ever been screened for cervical cancer, despite the majority having heard about the disease. Overall knowledge of cervical cancer was low, with many women unaware of its causes, risk factors and preventive measures. Key barriers to screening included a lack of awareness and insufficient medical advice. Factors significantly associated with lower odds of screening were being under age of 30 years, not having heard about cervical cancer, having no formal or only primary education and being single. There is an urgent need for community-based interventions to increase awareness and education about cervical cancer and to improve access to screening services, especially for younger, less educated and single women.